Oxford textbook of psychotherapy - Gabbard, G O; Beck, J S; Holmes, J (Oxford Oxford University Press, 2005)
This volume is an essential companion for every practising psychiatrist, clinical psychologist, psychotherapy counsellor, mental health nurse, psychotherapist, and mental health practitioner. Part one gives a comprehensive account of all the major psychotherapeutic approaches. Parts two and three systematically describe psychotherapeutic approaches to the major psychiatric disorders and personality disorders. Part four examines applications and modifications of psychotherapy across the lifecycle. Part five describes psychotherapy with specific populations such as medical patients and those where gender is an issue. Part six tackles some of the special topics including ethics, legal issues, and psychotherapy and neuroscience.
Keywords: Psychotherapy